APPLICATION OF NUMBERS LINE MEDIA ON ROUND NUMBER MATERIALS TO IMPROVE MATHEMATICAL LEARNING OUTCOMES STUDENT CLASS VI SD N 105425 MALASORI - Laurensia Masri Perangin Angin; Indah Nursela Sitorus (JURNAL HANDAYANI PGSD FIP UNIMED, 2020)
Abstract: The Application of Number Line Media on Round Number Material toImprove Mathematics Learning Outcomes of Students of Class VI SD N 105425Malasori. The purpose of the study was to improve student learning outcomes byapplying media line numbers on integer material in class VI SD N 105425Malasori. This study uses a Class Action Research design which consists of three stages: planning, implementing actions, and reflecting. The subjects of this study  were 30 students of grade VI SD N 105425 Malasori. The method applied in this  research is observation and test. While the data collection instruments use learning outcomes tests. Research data were analyzed quantitatively. The results of this study indicate that an increase in student learning outcomes by 13 , 23 %, from 78.57% in the first cycle to 91.80% in the second cycle. The conclusion of this study is that the learning of integer materials using number line media can improve student learning outcomes in grade VI SD 105425 Malasori. Therefore, teachers can use media in learning to improve student learning outcomes.   Keywords: Line number media; learning outcomes Abstract : Penerapan Media Garis Bilangan Pada Materi Bilangan Bulat UntukMeningkatkan Hasil Belajar Matematika Siswa Kelas VI SD N 105425 Malasori.Tujuan penelitian adalah untuk meningkatkan hasil belajar siswa dengan menerapkan media garis bilangan pada materi bilangan bulat di kelas VI SD N 105425 Malasori.  Penelitian ini menggunakan rancangan Penelitian Tindakan Kelas yang terdiri dari tiga tahap yaitu: perencanaan, pelaksanaan tindakan, dan refleksi. Subjek penelitian ini adalah 30 siswa kelas VI SD N 105425 Malasori. Metode yang diterapkan dalam penelitian ini adalah observasi dan tes. Sedangkan instrumen pengumpulan datanya menggunakan tes hasil belajar. Data penelitian dianalisis secara kuantitatif. Hasil penelitian ini menunjukkan  bahwa terjadi peningkatan hasil belajar siswa sebesar 13,23%, dari 78,57% pada siklus I menjadi 91,80% pada siklus II. Kesimpulan dari penelitian ini adalah bahwa pembelajaran materi bilangan bulat menggunakan media garis bilangan dapat meningkatkan hasil belajar siswa kelas VI SD 105425 Malasori. Oleh karena itu, guru dapat menggunakan media dalam pembelajaran untuk meningkatkan hasil belajar siswa.  Kata kunci: Media garis bilangan; hasil belajar